ONLINE REPORTING. - Neuts, Dana (Quill)
The article identifies online journalistic stories which won the 2011 Sigma Delta Chi Award from the Society of Professional Journalists. The Burlington Free Press covered the events that transpired during the Occupy movement in the city. Brenda Goodman and colleagues reported on the effect of gene therapy on hemophilia. Cam Simpson of Bloomberg News covered the child labor controversy surrounding Victoria's Secret.